Likelyhood of non-violent political action in societies fragmrnted by multiple conflicts: On the Colombian case (2010)
Ethere are societies fragmented by multi ple conflicts, close to war of all against all, characterized by authoritative and violent social relations, with a weak State nation and the propensity of some rulers to criminality and authoritarianism, and the presence of fragmentary tyrannies (warlords, guerrilla groups, and mafia). Such environment makes extremely difficult the adoption of nonviolent ways. This topic is analyzed in six sections: 1) proposal of the problem; 2) discussion on fragmentation and dissent in democracy and collective action; 3) relationshi p between non-violent political action and democracy; 4) synthesis of the Colombian situation; 5) some possibilities for the non-violent action in the country, ones proving to be adequate for fighting against violent and authoritatian state and non-state actors. © 2012 Instituto de Estudios Políticos y Relaciones Internacionales (IEPRI), Universidad Nacional de Colombia.